Ekstrak buah kaktus pir berduri menghambat pertumbuhan Staphylococcus aureus, Streptococcus mutans, dan Candida albicans Extract of cactus prickly pear inhibits the growing of Staphylococcus aureus, Streptococcus mutans, and Candida albicans - Irene Edith Rieuwpassa; Nurlindah Hamrun; St. Rahma Lukman; Reski Y. S; Soelistia Ramadhani (DiscoverSys Inc., 2013)
The study aimed to determine the effect of prickly pear cactus extract in inhibiting the growth of Staphylococcusaureus, Streptococcus mutans and Candida albicans. The laboratory experimental study using diffusion method. Theconcentration of the prickly pear cactus fruit extract used was 25%, 50%, 75%, 100%, whereas bacterial samplesderived from the laboratory of Microbiology, Faculty of Medicine, University of Hasanuddin. The observation ofseveral concentrations showed a decrease in the number of colonies contained S.aureus, S.mutans, C.albicanssignificant with increasing concentrations of the prickly pear cactus fruit extract. From these observations, thelargest inhibitory concentration present in a concentration of 100%. The conclusion is the fruit of the prickly pearcactus extract can inhibit the growth of S.aureus, S.mutans, and C.albicans. The higher the concentration of theextract, the more reduced the growth of S.aureus colonies, S.mutans, and C.albicans and vice versa.